2021
DOI: 10.2147/ijgm.s314611
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Breast and Thyroid Nodules: A Cross-Sectional Study

Abstract: Based on physical examination, to explore the relationship between breast mass (BM) and thyroid nodule (TN) prevalence, and to further explore other related factors that affect the occurrence of BM and TN. Methods: From January 1, 2018, to January 1, 2021, 12,538 female subjects received breast and thyroid ultrasound examinations at the same time in the health examination center of the Affiliated Hospital of North Sichuan Medical College. Univariate analysis and multivariate logistic analysis were used to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The high correlation between breast ultrasonography and thyroid cancer screening may also be due to the anatomical location and characteristics of the ultrasound examination. The breast and thyroid are anatomically located close to each other, and linear probes are commonly used for breast and thyroid ultrasound, making it easy to examine these organs together [ 26 ]. In contrast, given the use of a convex probe for abdominal or liver ultrasonography and the fact that the neck is not exposed, it is cumbersome to replace the probe and expose the neck to examine the thyroid gland [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high correlation between breast ultrasonography and thyroid cancer screening may also be due to the anatomical location and characteristics of the ultrasound examination. The breast and thyroid are anatomically located close to each other, and linear probes are commonly used for breast and thyroid ultrasound, making it easy to examine these organs together [ 26 ]. In contrast, given the use of a convex probe for abdominal or liver ultrasonography and the fact that the neck is not exposed, it is cumbersome to replace the probe and expose the neck to examine the thyroid gland [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Chinese study of 12,538 women undergoing simultaneous US breast and thyroid examination showed a bidirectional relationship between breast mass (BM) and TN, meaning that women with BM are at increased risk for TN and vice versa. Furthermore, thyroid hormone, in addition to being correlated with the onset of TN, also influences the development of BM [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid nodules are highly prevalent among the general population as a result of the rising detection rate of tiny and asymptomatic thyroid nodules by various imaging techniques (keh et al, 2015;Sreekumar et al, 2020). The prevalence of TN previously stated 50% when the nodules were detected by ultrasound and/or other radiologic techniques (Chen et al, 2013(Chen et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%